Building Information Modeling and simulation for the mechanical, electrical, and plumbing systems - Haiyan Xie; Tramel, J. M.; Wei Shi (2011 IEEE International Conference on Computer Science and Automation Engineering, 2011)
Building Information Modeling (BIM) can be implemented in estimating, clash detection, sustainability analysis, solutions to in-field Requests-For-Information, facility management, etc. This research focuses on implementing BIM throughout the entire construction life cycle. Currently, the Architectural/Engineering/Construction (A/E/C) companies are using BIM to realize improved productivity and cost-effectiveness. One benefit of using BIM applications is the enhanced interoperability, which will improve integrated building design and integrated project delivery (IPD). The accurate model of BIM has the ability to be used throughout the entire life cycle of the building, from initial design through occupancy and operation. The research will examine how to utilize the flexibility of the BIM/MEP (Mechanical, Electrical, and Plumbing) systems and how to reduce the overall impact of the built environment on human health and the natural environment by: efficiently using the MEP systems, protecting occupant health and improving employee productivity, as well as reducing waste, pollution and environmental degradation of healthcare buildings.